2008
DOI: 10.1016/j.actamat.2007.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Zr–(Cu,Ag)–Al bulk metallic glasses

Abstract: In this paper, we report the formation of a series Zr-(Cu,Ag)-Al bulk metallic glasses (BMGs) with diameters at least 20 mm and demonstrate the formation of about 25 g amorphous metallic ingots in a wide Zr-(Cu,Ag)-Al composition range using a conventional arc-melting machine. The origin of high glass-forming ability (GFA) of the Zr-(Cu,Ag)-Al alloy system has been investigated from the structural, thermodynamic and kinetic points of view. The high GFA of the Zr-(Cu,Ag)-Al system is attributed to denser local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
119
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(136 citation statements)
references
References 47 publications
13
119
2
2
Order By: Relevance
“…It has been found that microalloying with proper alloying elements can dramatically improve the GFA of various BMGs [23][24][25]. Previous studies showed that the GFA of Cu-, Mg-and ZrCu-based bulk metallic glasses were significantly enhanced by adding Ag [26][27][28][29]. In this work, Ag was also chosen as the doping element in the Zr 35 Ti 30 Cu 7.5 Be 27.5 system, which had a critical diameter of about 15 mm and a wide supercooled liquid region of 165.1 K [30].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that microalloying with proper alloying elements can dramatically improve the GFA of various BMGs [23][24][25]. Previous studies showed that the GFA of Cu-, Mg-and ZrCu-based bulk metallic glasses were significantly enhanced by adding Ag [26][27][28][29]. In this work, Ag was also chosen as the doping element in the Zr 35 Ti 30 Cu 7.5 Be 27.5 system, which had a critical diameter of about 15 mm and a wide supercooled liquid region of 165.1 K [30].…”
mentioning
confidence: 99%
“…From Figure 1(b), the best GFA was achieved for x = 1, which has a critical diameter of 20 mm. The enhanced GFA can probably be attributed to a denser local atomic packing and smaller differences in the Gibbs free energy between the amorphous and crystalline phases [29]. Therefore, the GFA of the Zr 35−x Ti 30 Cu 7.5 Be 27.5 Ag x (x=0-10) are x = 1x = 0x = 2x = 3x = 5x = 7x = 10.…”
mentioning
confidence: 99%
“…Recent interests in Copper and Zirconium based glassy alloys are driven by their high glassforming abilities [9][10][11][12][13][14] . Experimentally, the most common method to manufacture a metallic glass is by quenching the molten metallic liquid through the glass transition.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, over the past two decades, many Zr-based BMGs with the formula Zr-Al-TM have been successfully developed. 3,5,[10][11][12][13][14][15] The quaternary alloys in this system are summarized in Fig. 1; the elements linked with a solid line in the rectangular box represent the transition metals in the pre-existing quaternary alloys.…”
Section: Introductionmentioning
confidence: 99%